Large area blank for prosthetics and its manufacturing method
Patent Information
- Application Number
- JP2024543968
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-25
- Filing Date
- 2023-01-20
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-01-20
AI Technical Summary
【0024】 本発明による大面積ブランクは、大面積でありながら加工性に優れたワーク(workpiece)であって、切削加工時の加工性を改善することができるため、工具抵抗性及び摩耗率を減少させ、工具寿命を増加させることができ、加工時の辺縁部のチッピングを減少させることができ、一つのブランクを用いて多数の歯科修復物を必要に応じて間欠的又は順次に製作する上でブランクの利用効率を向上させることができ、歯科修復物の製作時の生産性を向上させることができ、加工された歯科修復物は、後熱処理条件を異にする簡易な工程を介してそれぞれ異なる透明性を有する高強度の歯科修復物に製造することができることにより、一つのブランクを介して多様なシェード(shade)を実現する歯科修復物を製造することができるので、物流管理の簡素化に寄与することができるという利点がある。
Smart Images

Figure 2025505121000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a large-area blank capable of producing a large number of prostheses through one blank, and in particular to a large-area blank having excellent machinability, and a method for manufacturing the same. [Background technology]
[0002] Materials and methods for manufacturing monolithic dental crowns using glasses containing lithium disilicate crystals have already been disclosed in many patents. However, in the known techniques, the crystal phase is large and difficult to machine immediately. For machining, a lithium metasilicate crystal phase, which is a machinable crystalline phase, is first formed and processed, and then a high-strength lithium disilicate crystal phase is formed by a secondary heat treatment. In this case, the accuracy of dimensions is reduced due to shrinkage caused by the post-heat treatment process, and a heat treatment process is added, which is troublesome. Generally, in the case of CAD / CAM prosthetic processing, a bulk body is directly processed in a hospital to manufacture a prosthetic, and the prosthetic must be tried on as quickly as possible (one-day appointment), so the time delay caused by the heat treatment process adds economical difficulties to patients and users.
[0003] In addition, existing lithium disilicate glass-ceramic materials have limitations in achieving high light transmittance and opalescence similar to those of natural teeth due to the coarse crystal phase.
[0004] In particular, existing lithium disilicate crystallized glass materials are primarily made into lithium metasilicate crystallized glass, which is easy to process, and then lithium disilicate is formed through a secondary crystallization heat treatment after processing to increase strength. At this time, the size of the crystal phase is about 3μm or more, so in this state, workability is significantly reduced and only strength is achieved.
[0005] In order to solve these problems, the applicant has proposed a method for manufacturing crystallized glass containing lithium disilicate crystal phase and silicate crystal phase, which has excellent processability, by adjusting the crystal size through temperature change in the first heat treatment, and has already received a patent (Korean Patent Registration No. 10-1975548). Specifically, the present invention discloses a method for producing dental crystallized glass, which includes a step of subjecting a glass composition containing 60-83% by weight of SiO2, 10-15% by weight of Li2O, 2-6% by weight of P2O5 acting as a nucleating agent, 1-5% by weight of Al2O3 increasing the glass transition temperature and softening point and promoting the chemical durability of the glass, 0.1-3% by weight of Sr increasing the softening point of the glass, 0.1-2% by weight of ZnO, 1-5% by weight of a colorant, and 2.5-6% by weight of a mixture of Na2O and K2O, which are alkali metal oxides that increase the thermal expansion coefficient of the glass, to a primary heat treatment at 400°C to 850°C, and a step of subjecting the primary heat treatment to a secondary heat treatment at 780°C to 880°C after the primary heat treatment, and discloses that a nano-sized lithium disilicate crystal phase and a silica crystal phase of 5nm to 2000nm are generated by the primary heat treatment, and the translucency is adjusted by the temperature of the secondary heat treatment. It was also confirmed that the crystallized glass obtained by the primary crystallization heat treatment has a crystal phase size of 5 to 2000 nm, and is a material that can be machined in the lithium disilicate state due to the precipitation of a silica crystal phase in addition to the lithium disilicate crystal phase, and that in terms of machining cutting force, the primary crystallization heat treatment is preferably performed at a temperature range of 480 to 800°C to have lithium disilicate and silica crystal phases with sizes of 30 to 500 nm.
[0006] Using such lithium disilicate glass as a workpiece, it has been possible to provide artificial teeth with improved physical properties and aesthetics through a simple post-heat treatment while improving the workability in machining performed by the consumer, i.e., a doctor or technician. The workpiece here is usually a blank in the form of a block, and when a prosthesis is obtained through one block, it has shown favorable results in terms of machinability. However, when it is actually provided as a large-area blank, for example, a large-area blank with a diameter of 60 mm or more and a thickness of 6 mm or more, there is a limit to the deterioration of workability through machining to the same degree as a block.
[0007] In particular, in the case of such large-area blanks, processability is an important factor in realizing the purpose for which artisans, the main consumers, require large-area blanks. If processability is not fully expressed, the utilization efficiency of the large-area blank will decrease significantly, making it difficult to realize the purpose of increasing the area of the blank. Furthermore, if workability declines, large-scale craftsmen, who are the main consumers of large-area blanks, may have to replace their processing burrs more quickly, resulting in reduced productivity.
[0008] One of the reasons why the same material shows differences in workability when made large is the machining environment. When processing one prosthesis through one block, wet grinding can be used, but in the case of large area blanks, multiple prostheses must be produced intermittently or sequentially from one blank according to the time required, so it is difficult to use the grinding method in the early stages of processing and a mill method must be used, which causes greater stress on the burrs and changes the way the burrs contact the blank.
[0009] Therefore, the inventors made great efforts to manufacture a large-area blank that is easy to process and can easily realize a prosthesis that satisfies the mechanical characteristics and aesthetics of a prosthesis made primarily of lithium disilicate glass ceramics. Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention seeks to provide a large-area blank that is excellent in workability. The present invention provides a method for producing a large-area blank with excellent workability by controlling heat treatment conditions using a specific glass composition. The present invention aims to provide a method for producing a prosthesis that has high strength and controlled translucency by machining a large-area blank to obtain a preform, and then converting the preform into a lithium disilicate-based crystal through subsequent heat treatment. [Means for solving the problem]
[0011] One embodiment of the present invention provides a large-area blank having a major axis length of at least 60 mm and a thickness of at least 6 mm, in which an X-ray diffraction analysis pattern using CuKα radiation shows no crystalline phase peak within the range of 2θ (degrees) 10 to 70, and the crystallinity is 0.00%, but SEM analysis confirms that crystalline particles having an average particle size of 10 to 70 nm are dispersed within an amorphous SiO2-Li2O-Al2O3-based glass matrix.
[0012] In the large area blank according to one embodiment of the present invention, the SiO2-Li2O-Al2O3-based glass matrix may have an amorphous bump in the X-ray diffraction analysis pattern using CuKα radiation within the range of 2θ (degree) 21 to 22.
[0013] In the large area blank according to the present invention, the length of the major axis may be 60 to 150 mm, and the thickness may be 6 to 20 mm.
[0014] In the large area blank according to the present invention, the SiO2-Li2O-Al2O3 based glass matrix may contain 69.0-75.0% by weight of SiO2, 12.0-14.0% by weight of Li2O, 2.5-3.5% by weight of Al2O3, 0.12-0.22% by weight of ZnO, 1.1-2.7% by weight of K2O, 0.1-0.3% by weight of Na2O, and 2.0-6.0% by weight of P2O5.
[0015] Large area blanks according to the invention may have a light transmission of at least 80% at a wavelength of 550 nm based on a thickness of 1.2 mm.
[0016] Preferably, the large area blank may have a light transmittance of 80-90% at a wavelength of 550 nm based on a thickness of 1.2 mm.
[0017] The present invention also provides a method for producing a pre-blank having a predetermined shape and a major axis length of at least 60 mm and a thickness of at least 6 mm, comprising the steps of melting a glass composition containing 69.0-75.0 wt% SiO2, 12.0-14.0 wt% Li2O, 2.5-3.5 wt% Al2O3, 0.12-0.22 wt% ZnO, 1.1-2.7 wt% K2O, 0.1-0.3 wt% Na2O, and 2.0-6.0 wt% P2O5, forming the glass composition in a mold, cooling the glass composition, and annealing the glass composition at a predetermined rate from 465°C to 280°C for 20 minutes to 2 hours, and
[0018] and heat treating the preliminary blank in a furnace starting from a temperature of 300° C. and increasing to a maximum temperature of 400 to 500° C. for 1 to 24 hours.
[0019] The present invention also includes the steps of: manufacturing a predetermined dental restoration by machining the large area blank according to the one embodiment; and heat treating the dental restoration to adjust its translucency;
[0020] The present invention provides a method for manufacturing a dental restoration, wherein the translucency adjusting step is at least one step selected from a high translucency adjusting step of performing heat treatment at a maximum temperature in the range of 790°C or more and less than 810°C for 5 to 30 minutes, a medium translucency adjusting step of performing heat treatment at a maximum temperature in the range of 810°C or more and less than 825°C for 5 to 30 minutes, a low translucency adjusting step of performing heat treatment at a maximum temperature in the range of 825°C or more and less than 845°C for 5 to 30 minutes, and a medium opacity adjusting step of performing heat treatment at a maximum temperature in the range of 845°C or more and 860°C for 5 to 30 minutes.
[0021] In the manufacturing method for a dental restoration according to another embodiment of the present invention, the high light transmittance adjustment step may be a step of achieving an average light transmittance of 45 to 55%. In the method for manufacturing a dental restoration according to another embodiment of the present invention, the intermediate translucency adjustment step may be a step of achieving an average light transmittance of 35 to 44%. In the manufacturing method for a dental restoration according to another embodiment of the present invention, the low light transmittance adjustment step may be a step of achieving an average light transmittance of 18 to 34%. In the manufacturing method for a dental restoration according to another embodiment of the present invention, the semi-translucency adjustment step may be a step of achieving an average light transmittance of 13 to 17%.
[0022] The present invention also provides a dental restoration obtainable by the manufacturing method of one of the above embodiments, comprising a crystalline phase in an amorphous glass matrix, the crystalline phase comprising a predominant crystalline phase of lithium disilicate and an additional crystalline phase comprising at least one crystalline phase selected from the group consisting of cristobalite, tridymite, quartz, eucryptite, spodumene, virgilite and mixtures thereof, and having a biaxial flexural strength of at least 380 MPa.
[0023] In one embodiment, the dental restoration may be selected from a crown, an inlay, an onlay, and a veneer. Effect of the Invention
[0024] The large-area blank according to the present invention is a workpiece having excellent processability despite its large area, and since it can improve processability during cutting, it can reduce tool resistance and wear rate and increase tool life, and can reduce chipping of the edges during processing. It can improve the utilization efficiency of a blank when a plurality of dental restorations are intermittently or sequentially manufactured using one blank as needed, and can improve productivity in manufacturing dental restorations. The processed dental restorations can be manufactured into high-strength dental restorations having different transparencies through a simple process with different post-heat treatment conditions, and thus dental restorations realizing various shades can be manufactured using a single blank, which has the advantage of contributing to simplification of logistics management. [Brief description of the drawings]
[0025] [Figure 1] 1 is a graph showing the results of X-ray diffraction analysis of a large-area blank of the present invention. [Diagram 2] 1 is a scanning electron microscope (SEM) photograph showing the microstructure and crystalline phase size of a large area blank of the present invention. [Diagram 3] 1 is a transmission measurement graph for a large area blank of the present invention. [Figure 4] 1 is a comparative graph of cutting resistance for large area blanks of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] The above and further aspects of the present invention will become more apparent through the description of preferred embodiments with reference to the accompanying drawings. The following detailed description will enable those skilled in the art to easily understand and realize the present invention through such embodiments.
[0027] One embodiment of the present invention provides a large-area blank having a major axis length of at least 60 mm and a thickness of at least 6 mm, in which an X-ray diffraction analysis pattern using CuKα radiation shows no crystalline phase peak within the range of 2θ (degrees) 10 to 70, and the crystallinity is 0.00%, but SEM analysis confirms that crystalline particles having an average particle size of 10 to 70 nm are dispersed within an amorphous SiO2-Li2O-Al2O3-based glass matrix.
[0028] In particular, in the large-area blank of the present invention, the amorphous SiO2-LiO-Al2O3-based glass matrix may have an amorphous bump in an X-ray diffraction analysis pattern using CuKα radiation within the range of 2θ (degree) 21 to 22, specifically within the range of 21.9 to 22.0.
[0029] In the above and following descriptions, X-ray diffraction analysis is defined as the results of analysis using an X-ray diffraction analyzer (D / MAX-2500, Rigaku Corporation, Japan; CuKα (40 kV, 60 mA), scanning speed: 6° / min, 2θ: 10 to 70 (degrees), Rigaku Corporation, Japan).
[0030] In the above and following descriptions, "crystallinity" can be defined as the ratio of a crystalline phase to an amorphous glass matrix, which can be determined by various methods. In one embodiment of the present invention, the crystallinity is defined as a value automatically calculated by the X-ray diffraction analysis defined above.
[0031] The XRD analysis result graph for a large area blank according to a preferred embodiment is shown in FIG.
[0032] As shown in FIG. 1, in the case of the large area blank according to the present invention, there is no peak of a crystalline phase within the range of 2θ10 to 70 in the X-ray diffraction analysis pattern, and the crystallinity is 0.00%. From these results, it can be predicted that no crystalline phase exists in the body containing the amorphous SiO2-Li2O-Al2O3 glass matrix.
[0033] Generally, various crystal phases may exist in a glass composition that realizes a SiO2-Li2O-Al2O3-based glass matrix, examples of which include lithium phosphate, lithium (meta)silicate, lithium disilicate, cristobalite, tridymite, quartz, eucryptite, spodumene, virgilite, etc. In particular, the main crystal phase may generally include lithium (meta)silicate or lithium disilicate.
[0034] However, in the case of the large-area blank according to the present invention, there are no crystalline phase peaks other than the amorphous peaks that can be defined by the amorphous SiO2-Li2O-Al2O3-based glass matrix, and the crystallinity related to the content of such crystalline matter is 0.00%, and from these results, it can be predicted that the blank is made of pure amorphous glass without any crystalline matter. However, the large-area blank according to the present invention shows a different behavior from glass made only of the amorphous SiO2-Li2O-Al2O3-based glass matrix, and this difference can be confirmed from the results of analysis using SEM.
[0035] FIG. 2 is an SEM observation image (magnification of ×100K) of a large area blank of the present invention, clearly showing the presence of particles. From the SEM observation results shown in FIG. 2, it can be confirmed that particles with an average particle size of 10 to 70 nm are dispersed.
[0036] The average size of the crystalline phase particles can be derived from the SEM photograph, specifically, by the linear intercept method, in which diagonal or random lines are drawn on the SEM photograph, and the number of crystalline phases through which the lines pass is divided by the length of the lines, taking into account the magnification. In the above and following description, the average grain size of the crystalline phase is understood to be calculated by such a method.
[0037] The large-area blank according to the present invention shows the result of the X-ray diffraction analysis pattern shown in FIG. 1 and the SEM observation image shown in FIG. 2 being mutually arranged, and such characteristics can be inferred in various cases. For example, it may be a state in which low crystallinity or amorphous fine non-stoichiometric crystalline is formed as a step corresponding to the initial crystallization of glass. Even though fine particles are observed in the SEM observation image shown in FIG. 2, no crystalline phase peak is detected in the X-ray diffraction analysis pattern shown in FIG. 1, and it can be predicted that the crystallinity is analyzed to be 0.00%. However, the mechanism for such characteristics is not limited thereto, and it is not intended to limit the technical significance of the large-area blank according to the present invention by such an unexplained mechanism.
[0038] Due to the specific structure associated with the elucidation of the inter-arranged particles, the large-area blank of the present invention, despite its large area with a major axis length of at least 60 mm and a thickness of at least 6 mm, can be expected to exhibit excellent workability in machining using mill equipment, particularly in dry milling by using a single large-area blank to cut multiple dental restorations intermittently or sequentially as necessary.
[0039] In particular, as can be seen from the SEM image in Figure 2, particles with an average particle size of 10 to 70 nm are dispersed within the glass matrix, and this is an extremely fine crystalline phase with a crystal size 50 to 300 times smaller than that of conventional CAD / CAM workpieces (ingots and block products that are not large-area blanks), which usually have lithium metasilicate as the main crystalline phase. It can be estimated that this extremely fine crystalline phase had a significant effect on the workability of the large-area blanks.
[0040] In the above and following descriptions, the shape of the large-area blank is not limited, and because there is no such shape limitation, it is described in terms of major axis instead of diameter, and when taking into account the length and thickness of the major axis, it may have an outer shape that is normally called a disk.
[0041] In a preferred embodiment of the present invention, the large-area blank has a major axis length of 60 to 150 mm and a thickness of 6 to 20 mm, which is preferable in that this reduces the occurrence of defects in machining and provides compatibility for mass machining of the blanks.
[0042] On the other hand, the large-area blank according to a preferred embodiment of the present invention contains an amorphous SiO2-Li2O-Al2O3-based glass matrix, specifically containing 69.0-75.0% by weight of SiO2, 12.0-14.0% by weight of Li2O, 2.5-3.5% by weight of Al2O3, 0.12-0.22% by weight of ZnO, 1.1-2.7% by weight of K2O, 0.1-0.3% by weight of Na2O, and 2.0-6.0% by weight of P2O. Although it is a large-area blank, it has excellent processability and is preferable in terms of machining the large-area blank to obtain a dental restoration, and then realizing this into a dental restoration that satisfies the desired strength and aesthetics by a simple heat treatment method.
[0043] In addition, the large-area blank according to the present invention has a light transmittance of at least 80% at a wavelength of 550 nm based on a thickness of 1.2 mm, preferably at least 80-90% at a wavelength of 550 nm based on a thickness of 1.2 mm, which is preferable in that it has excellent machinability while easily controlling the transmittance of the dental restoration obtained by machining and can satisfy the desired aesthetics. More specifically, the large-area blank showing such a light transmittance is formed of extremely fine crystal particles, which are then preferable in that they have the property of being able to provide dental restorations with various mechanical properties and light transmittance while showing various sizes and size distributions depending on the temperature.
[0044] FIG. 3 shows a graph of the measured light transmission of a large area blank according to the invention. Characteristically, in the case of the large-area blank obtained by the present invention, the resistance generated in the tool during processing using a processing machine can be significantly reduced, and as a specific example, a large-area blank having the characteristics shown in Figures 1 and 2 was processed in the form of a dental premolar using a dental processing machine (PM-5, PISTIS, Korea) and the degree of tool wear was measured. The measurement results are shown in Figure 4.
[0045] From the results in FIG. 4, in the case of the large-area blank of the present invention, in spite of its large area, it was confirmed that the tool life was improved by 75% compared to the existing large-area blank of the same specification (manufactured using the company's own block material) made of crystallized glass with lithium disilicate as the main crystal phase, and that it was machined without chipping at the edges.
[0046] On the other hand, as described above, the large-area blank according to the present invention may have a glass matrix containing SiO2 69.0-75.0% by weight, Li2O 12.0-14.0% by weight, Al2O3 2.5-3.5% by weight, ZnO 0.12-0.22% by weight, K2O 1.1-2.7% by weight, Na2O 0.1-0.3% by weight, and P2O 5 2.0-6.0% by weight. The glass composition constituting such a glass matrix precipitates a crystalline phase in the amorphous glass matrix through crystal nucleation and crystal growth heat treatment, but the above-mentioned glass matrix corresponds to a temperature at which crystal nuclei and crystal growth occur at 400°C to 880°C. That is, crystal nuclei begin to form at a minimum of 400°C, and crystal growth occurs as the temperature rises, and this crystal growth shows the lowest light transmittance when used as an artificial tooth at a maximum of 880°C. In other words, the translucency gradually decreases from the temperature at which the crystals grow up to a maximum of 880°C. In consideration of this crystal growth pattern, if a bulk block is obtained by growing crystals so that the bulk block has high strength while also having workability that allows machining, and then one of the obtained bulk blocks is machined, and then the transparency can be adjusted by post-heat treatment under various conditions, taking into account the required trial position or the unique color of the patient's teeth, this will ultimately contribute to simplifying logistics management.
[0047] Since natural teeth, not only each tooth but all teeth, have various translucencies and the required translucency may differ depending on the patient and the trial position, if it is possible to realize various changes in transparency according to the heat treatment temperature using one bulk block, it is possible to provide artificial teeth that satisfy various aesthetic requirements using a small amount of work. Furthermore, if it is a large-area blank that can provide many artificial teeth using one blank, it goes without saying that it will contribute greatly to simplifying logistics management.
[0048] From this viewpoint, the present invention provides a method for manufacturing a large-area blank, comprising the steps of melting a glass composition containing 69.0-75.0% by weight of SiO2, 12.0-14.0% by weight of Li2O, 2.5-3.5% by weight of Al2O3, 0.12-0.22% by weight of ZnO, 1.1-2.7% by weight of K2O, 0.1-0.3% by weight of Na2O, and 2.0-6.0% by weight of P2O5, forming the glass composition in a mold, cooling the glass composition, and annealing the glass composition at a predetermined speed from 465°C to 280°C for 20 minutes to 2 hours, thereby producing a blank having a predetermined shape with a long axis length of at least 60 mm and a thickness of at least 6 mm, and heat treating the blank in a furnace starting from a temperature of 300°C and increasing to a maximum temperature of 400-500°C for 1 to 24 hours.
[0049] In one specific embodiment of the present invention, first, a glass composition containing 69.0 to 75.0 wt% of SiO2, 12.0 to 14.0 wt% of Li2O, 2.5 to 3.5 wt% of Al2O3, 0.12 to 0.22 wt% of ZnO, 1.1 to 2.7 wt% of K2O, 0.1 to 0.3 wt% of Na2O, and 2.0 to 6.0 wt% of P2O5 is weighed and mixed.
[0050] Li2CO3 may be added to the glass composition instead of Li2O, and carbon dioxide (CO2), which is the carbon (C) component of Li2CO3, is discharged as a gas and escapes during the glass melting process. K2CO3 and Na2CO3 may be added to the alkali oxide instead of K2O and Na2CO3, respectively, and carbon dioxide (CO2), which is the carbon (C) component of K2CO3 and Na2CO3, is discharged as a gas and escapes during the glass melting process.
[0051] The mixing is performed by a dry mixing process, and the dry mixing process may be a ball milling process. The ball milling process is specifically described as follows: the starting materials are charged into a ball milling machine, and the ball milling machine is rotated at a constant speed to mechanically crush the starting materials and mix them uniformly. The balls used in the ball milling machine may be made of ceramic materials such as zirconia or alumina, and the balls may all be the same size or may have at least two sizes. The ball size, milling time, and rotation speed of the ball milling machine per minute are adjusted in consideration of the target particle size. For example, the ball size may be set in the range of about 1 mm to 30 mm, and the rotation speed of the ball milling machine may be set in the range of about 50 to 500 rpm in consideration of the particle size. The ball milling is preferably performed for 1 to 48 hours in consideration of the target particle size. The starting materials are crushed into fine particles by the ball milling machine, and the particles have a uniform particle size and are mixed uniformly.
[0052] The mixed starting materials are placed in a melting furnace, and the melting furnace containing the starting materials is heated to melt the starting materials. Here, melting means that the starting materials are changed from a solid state to a liquid state having a viscous substance. The melting furnace is preferably made of a material that has a high melting point, high strength, and a low contact angle to prevent the molten material from sticking together. For this reason, it is preferable that the melting furnace is made of a material such as platinum (Pt), diamond-like carbon (DLC), chamotte, etc., or the surface of the melting furnace is coated with a material such as platinum (Pt) or diamond-like carbon (DLC).
[0053] The melting is preferably carried out at 1,400 to 2,000°C at normal pressure for 1 to 12 hours. When the melting temperature is less than 1,400°C, the starting materials may not melt yet, and when the melting temperature exceeds 2,000°C, excessive energy consumption is required, which is not economical, so it is preferable to melt at a temperature in the above-mentioned range. In addition, when the melting time is too short, the starting materials may not melt sufficiently, and when the melting time is too long, excessive energy consumption is required, which is not economical. The temperature rise rate of the melting furnace is preferably about 5°C / min to 50°C / min, but when the temperature rise rate of the melting furnace is too slow, it takes a long time and the productivity decreases, and when the temperature rise rate of the melting furnace is too fast, the amount of volatilization of the starting materials increases due to a sudden temperature rise, which may result in poor physical properties of the crystallized glass, so it is preferable to raise the temperature of the melting furnace at a temperature rise rate in the above-mentioned range. The melting is preferably carried out in an oxidizing atmosphere such as oxygen (O2) or air.
[0054] The molten material is poured into a mold that is determined to obtain a dental crystallized glass of a desired shape and size. The mold is preferably made of a material that has a high melting point, high strength, and a low contact angle to prevent the glass melt from sticking to it. For this reason, the mold is preferably made of a material such as graphite or carbon, and is preheated to 200 to 300°C to prevent thermal shock before pouring the molten material into the mold.
[0055] Since the molten material in the mold is molded and cooled, it is preferable to carry out an annealing step after the cooling process, in which the temperature is gradually decreased from 465°C to 280°C for 20 minutes to 2 hours at a predetermined rate, preferably at a rate of 1.5°C / min to 10°C / min.
[0056] This slow cooling step reduces stress deviations, preferably eliminates stress, within the molded product, which can have a desirable effect on controlling the size of the crystal phase and improving the uniformity of the crystal distribution in the subsequent crystallization step.
[0057] The molded product (a preliminary blank with a major axis length of at least 60 mm and a thickness of at least 6 mm) that has undergone this slow cooling process is transferred to a crystallization heat treatment furnace for nucleation and crystal growth to produce the desired crystallized glass.
[0058] In this case, the crystallization heat treatment is performed by a method in which the blank is heat-treated for 1 to 24 hours from a furnace temperature of 300° C. to a maximum temperature of 400 to 500° C. As a result, a large-area blank can be obtained in which no crystalline phase peak exists within the range of 2θ10 to 70 in an X-ray diffraction analysis pattern using CuKα radiation, the crystallinity is 0.00%, but analysis by SEM confirms that crystalline particles with an average particle size of 10 to 70 nm are dispersed in an amorphous SiO2-Li2CO-Al2O3-based glass matrix, and the length of the major axis is at least 60 mm and the thickness is at least 6 mm.
[0059] In this case, the heat treatment is performed for 1 to 24 hours starting from a furnace temperature of 300°C to a maximum temperature of 400 to 500°C. If the temperature range is higher or the heat treatment time is longer, the machinability of the obtained large-area blank may decrease and the light transmittance may deviate from the desired range, which is not preferable.
[0060] As described above, according to the present invention, in the X-ray diffraction analysis pattern using CuKα radiation, there is no crystalline phase peak within the range of 2θ10-70, and the crystallinity is 0.00%, but in the analysis by SEM, it is confirmed that crystalline particles with an average particle size of 10-70 nm are dispersed in an amorphous SiO2-Li2O-Al2O3-based glass matrix, and the large-area blank with a long axis length of at least 60 mm and a thickness of at least 6 mm has the property that the crystalline phase shows various sizes and size distributions depending on the temperature, thereby realizing various mechanical properties and optical transparency.
[0061] The large-area blank obtained by such a method can exhibit different properties in terms of the optical transparency of the material depending on the temperature range of the heat treatment.
[0062] The large-area blank is used as a workpiece for machining such as CAD / CAM processing. Conventional crystallized glass generally has a coarse crystal size, making it difficult to adjust the translucency, and is also strong and difficult to process. In contrast, the large-area blank of the present invention contains extremely fine crystals, which show various sizes and size distributions depending on the temperature, and each of which can exhibit various physical properties and transparency. Taking this into account, a large-area blank is manufactured from one glass composition, and the resulting large-area blank is machined, and the transparency of the resultant product can be controlled depending on the heat treatment conditions.
[0063] However, in the case of the large-area blank according to the present invention, since consideration is given to processability, it is preferable that the realization of various mechanical properties and optical transparency is carried out after the blank is fabricated into a dental restoration.
[0064] From this viewpoint, the present invention provides a method for manufacturing a dental restoration, comprising the steps of: manufacturing a predetermined dental restoration by cutting the large-area blank according to the embodiment; and heat-treating the dental restoration to adjust translucency, wherein the step of adjusting translucency is at least one step selected from a high translucency adjusting step of performing heat treatment at a maximum temperature in the range of 790°C or more and less than 810°C for 5 minutes to 30 minutes, a medium translucency adjusting step of performing heat treatment at a maximum temperature in the range of 810°C or more and less than 825°C for 5 minutes to 30 minutes, a low translucency adjusting step of performing heat treatment at a maximum temperature in the range of 825°C or more and less than 845°C for 5 minutes to 30 minutes, and a semi-translucency adjusting step of performing heat treatment at a maximum temperature in the range of 845°C or more and 860°C for 5 minutes to 30 minutes.
[0065] As an example, after a large-area blank is cut to obtain a desired dental restoration, a high translucency adjustment step is performed in which heat treatment is performed for 5 to 30 minutes at a maximum temperature of 790° C. or higher and lower than 810° C., and an average light transmittance of 45 to 55% can be achieved. Dental restorations having such high translucency can be useful as inlays and onlays, but are not limited thereto.
[0066] The large area blank according to another embodiment of the present invention can achieve an average light transmittance of 35 to 44% through an intermediate translucency adjustment step in which the blank is heat-treated for 5 to 30 minutes at a maximum temperature in the range of 810° C. to 825° C. Dental restorations that satisfy such medium translucency may be useful for coloring purposes, but are not limited thereto.
[0067] The large area blank according to another embodiment of the present invention can achieve an average light transmittance of 18 to 34% through a low translucency adjustment step in which the blank is heat-treated for 5 to 30 minutes at a maximum temperature in the range of 825° C. to 845° C. In the case where the blank has such low translucency, the blank can be useful for applications such as posterior crowns, but is not limited thereto.
[0068] The large area blank according to another embodiment of the present invention can achieve an average light transmittance of 13 to 17% through a translucency adjustment step in which the blank is heat-treated for 5 to 30 minutes at a maximum temperature in the range of 845°C to 860°C. A dental restoration having such translucency (medium opacity) can be useful for applications such as, but not limited to, restoring discolored teeth. In the above and following descriptions, the light transmittance was measured using a UV-visible spectrometer (UV-2401PC, Shimadzu Corporation, Japan).
[0069] In measuring the light transmittance of the large-area blank and dental restoration according to the present invention, the surface of the specimen was wiped clean with ethanol and measured using a UV-visible spectrometer (UV-2401PC, Shimadzu Corporation, Japan). The measurement wavelength range was 300-800 nm, and the slit width was 2.0 nm. The average light transmittance can be defined as the average value of the light transmittance values in the entire wavelength range. In the above and following descriptions, the light transmittance can be defined as a value based on a specimen thickness of 1.2 mm.
[0070] The dental restoration according to the present invention can express the above-mentioned various light transmittances through heat treatment after cutting, making it possible to provide a large number of dental restorations from a single blank, and furthermore, by providing dental restorations having low to high translucency (including intermediate levels of opacity), it is possible to realize more than 80 different shades. The dental restorations thus obtained can be provided as trial positions or as various dental restorations with transparency adjusted by the patient. This makes it possible to provide dental restorations that are able to withstand the bite force of molars while achieving a variety of transparencies and improved aesthetics.
[0071] According to the present invention, through such a manufacturing method, a dental restoration can be obtained, which is a glass-ceramic body comprising a crystalline phase in an amorphous glass matrix, the crystalline phase comprising a main crystalline phase of lithium disilicate and at least one additional crystalline phase selected from the group consisting of cristobalite, tridymite, quartz, eucryptite, spodumene, virgilite and mixtures thereof, and has a biaxial bending strength of at least 380 MPa.
[0072] In the above and following description, the term predominant crystalline phase is defined as a crystalline phase that occupies at least 80% by weight of the total crystalline phase, and the term additional crystalline phase may be defined as the remaining crystalline phase of the total crystalline phase that is not the predominant crystalline phase.
[0073] The content of the crystalline phase can be calculated by X-ray diffraction analysis. For example, in a specimen consisting of two polymorphic phases a and b, the ratio of crystalline phase a to the total polymorphic phase F is a is quantitatively expressed by the following Equation 1.
[0074] TIFF2025505121000002.tif26166
[0075] This value can be determined by measuring the intensity ratio of the two crystalline phases and obtaining a constant K, which is the absolute intensity ratio I oa / I ob and is determined by measuring a standard substance. In the above and following descriptions, the term "main crystalline phase" can be defined as being set based on the content calculated by such a method. The biaxial flexure strength here is the biaxial flexure strength based on ISO6872.
[0076] In order to confirm the change in biaxial bending strength depending on the heat treatment conditions, test pieces with a diameter of 11.9 mm and a thickness of 1.18 mm were prepared from the large area blanks described above, and then post-heat-treated under different heat treatment conditions to obtain the respective test pieces. The biaxial bending strength of the test pieces was measured according to ISO6872, and the results are shown in Tables 1 to 4 below.
[0077] In the following Tables 1 to 4, in the heat treatment conditions, HT indicates a specimen obtained by heat treatment for 5 to 30 minutes at a maximum temperature of 790°C or more and less than 810°C, MT indicates a specimen obtained by heat treatment for 5 to 30 minutes at a maximum temperature of 810°C or more and less than 825°C, LT indicates a specimen obtained by heat treatment for 5 to 30 minutes at a maximum temperature of 825°C or more and less than 845°C, and MO indicates a specimen obtained by heat treatment for 5 to 30 minutes at a maximum temperature of 845°C or more and 860°C.
[0078] [Table 1]
[0079] [Table 2]
[0080] [Table 3]
[0081] [Table 4]
[0082] As shown in Tables 1 to 4 above, in the case of the large-area blank of the present invention, the strength can be controlled depending on the conditions of the post-heat treatment after cutting, and it can be seen that such strength can satisfy the appropriate level for dental restorations.
[0083] In the above and following description, the dental restoration may be selected from, but is not limited to, a crown, an inlay, an onlay and a veneer.
[0084] The present invention has been described with reference to one embodiment shown in the drawings, but this is by way of example only, and various modifications and equivalent alternative embodiments are possible for those skilled in the art. [Industrial Applicability]
[0085] The present invention relates to a large-area blank capable of producing a large number of prostheses through one blank, and in particular to a large-area blank having excellent machinability, and a method for manufacturing the same.
[0086] The large-area blank according to the present invention is a workpiece having excellent processability despite its large area, and can improve processability during cutting, thereby reducing tool resistance and wear rate and increasing tool life; it can reduce chipping of the edges during processing; it can improve the utilization efficiency of a single blank when a plurality of dental restorations are intermittently or sequentially manufactured as needed using the same blank, thereby improving productivity in the manufacture of dental restorations; and it has the advantage that the processed dental restorations can be manufactured into high-strength dental restorations having different transparencies through a simple process with different post-heat treatment conditions, and therefore dental restorations realizing various shades can be manufactured using a single blank, which can contribute to simplifying logistics management.
Claims
1. In the X-ray diffraction analysis pattern using CuKα radiation, there is no peak of a crystalline phase within the range of 2θ (degrees) 10 to 70, and the crystallinity is 0.00%, but in the analysis by SEM, crystalline particles with an average particle size of 10 to 70 nm are present, and the amorphous SiO 2 -Li 2 O-Al 2 O 3 It was confirmed that the nanoparticles were dispersed in the glass matrix. The length of the major axis is at least 60 mm and the thickness is at least 6 mm. A large area blank characterized by:
2. SiO 2 -Li 2 O-Al 2 O 3 The glass matrix has an amorphous bump in the X-ray diffraction analysis pattern of an amorphous phase within the range of 2θ (degrees) 21 to 22 in a CuKα ray diffraction analysis pattern.
2. The large area blank of claim 1.
3. The length of the major axis is 60 to 150 mm, and the thickness is 6 to 20 mm.
2. The large area blank of claim 1.
4. SiO 2 -Li 2 O-Al 2 O 3 The glass matrix is SiO 2 69.0-75.0% by weight, Li 2 O12.0-14.0% by weight, Al 2 O 3 2.5-3.5% by weight, ZnO 0.12-0.22% by weight, K 2 O1.1-2.7% by weight, Na 2 O 0.1 to 0.3% by weight and P 2 O 5 Contains 2.0 to 6.0% by weight 2. The large area blank of claim 1.
5. 1. The light transmittance is at least 80% at a wavelength of 550 nm based on a thickness of 2 mm.
2. The large area blank of claim 1.
6. Based on a thickness of 1.2 mm, the light transmittance is 80-90% at a wavelength of 550 nm.
6. A large area blank according to claim 1 or 5.
7. SiO 2 69.0-75.0% by weight, Li 2 O12.0-14.0% by weight, Al 2 O 3 2.5-3.5% by weight, ZnO 0.12-0.22% by weight, K 2 O1.1-2.7% by weight, Na 2 O 0.1 to 0.3% by weight and P 2 O 5 2.0-6.0 wt. % of a glass composition, melting it in a mold, forming and cooling it, and annealing it at a predetermined rate from 465° C. to 280° C. for 20 minutes to 2 hours to produce a blank of a predetermined shape having a major axis length of at least 60 mm and a thickness of at least 6 mm; and heat treating the blank in a furnace for 1 hour to 24 hours starting at 300° C. and increasing to a maximum temperature of 400-500° C. A method for manufacturing a large area blank, comprising:
8. A step of manufacturing a predetermined dental restoration by machining the large area blank according to claim 1; and heat treating the dental restoration to adjust its translucency; The step of adjusting the translucency includes a high translucency adjustment step of performing heat treatment at a maximum temperature of 790° C. or more and less than 810° C. for 5 minutes to 30 minutes; an intermediate translucency adjusting step of performing heat treatment at a maximum temperature in the range of 810° C. or more and less than 825° C. for 5 minutes to 30 minutes; A low light transmittance adjusting step of performing heat treatment at a maximum temperature in the range of 825°C or more and less than 845°C for 5 minutes to 30 minutes; and At least one step selected from the semi-permeability adjustment step of heat-treating at a maximum temperature in the range of 845°C to 860°C for 5 to 30 minutes. A method for producing a dental restoration comprising the steps of:
9. The high light transmittance adjustment step is a step to achieve an average light transmittance of 45-55%. A method for producing a dental restoration according to claim 8.
10. The intermediate light transmittance adjustment step is to achieve an average light transmittance of 35-44%. A method for producing a dental restoration according to claim 8.
11. The low light transmittance adjustment step is a step to achieve an average light transmittance of 18-34%. A method for producing a dental restoration according to claim 8.
12. The semi-translucent adjustment step is a step to achieve an average light transmittance of 13-17%. A method for producing a dental restoration according to claim 8.
13. A glass-ceramic body comprising a crystalline phase in an amorphous glass matrix, the glass-ceramic body being obtainable by the method according to any one of claims 8 to 12, The crystalline phase includes a main crystalline phase being lithium disilicate, and an additional crystalline phase including at least one crystalline phase selected from cristobalite, tridymite, quartz, eucryptite, spodumene, virgilite, and mixtures thereof; Biaxial bending strength is at least 380 MPa A dental restoration characterized by:
14. The dental restoration is selected from crowns, inlays, onlays and veneers.
14. A dental restoration according to claim 13.
Citation Information
Patent Citations
Low crystallinity glass-ceramic
JP2017509574A
Lithium silicate low temperature quartz glass ceramic
JP2018526317A
Zirconia reinforced glass ceramic
JP2019522620A
Dental bulk block for grinding processing and method of manufacturing the same
JP2020193191A